Elimination of tuberculosis requires prior control of silicosis including sub-radiological silicosis - Singh, Dharmendra; Sarkar, Bidisa; Sarkar, Kamalesh (Indian journal of tuberculosis, 2023)
India is committed to the elimination of tuberculosis by 2025. But its achievement appears to be difficult as India has a huge burden of silicosis as well as sub-radiological silicosis, which was never given its required attention. Silicotic subjects are highly vulnerable to pulmonary tuberculosis due to the progressive decline of lung immunity. A study among vulnerable glass factory workers in Firozabad, Uttar Pradesh, revealed that silicotic workers were 7.5 times more at risk of pulmonary tuberculosis compared to non-silicotic subjects. Since India has a huge burden of silicosis and sub-radiological silicosis, the elimination of tuberculosis needs prior attention on silicosis. This article may be viewed as an eye-opener for understanding the necessity of dual control of both silicosis as well as tuberculosis by integrating both together. •The article has evidenced that silicotic subjects are highly vulnerable to silicotuberculosis due to declined lung immunity.•Considering India’s commitment to the elimination of TB by 2025, achieving it is difficult unless silicosis is controlled.•India has a huge burden of silicosis & sub-radiological silicosis. A sizable number of hidden TB cases are within them.•ICMR has identified a proxy biomarker, which may be used for the early detection of silicosis of workers for intervention.